Cocoa programming for Mac OS X - Hillegass, Aaron (Addison-Wesley, 2008)
The best-selling introduction to Cocoa, once again updated to cover the latest Mac programming technologies, and still enthusiastically recommended by experienced Mac OS X developers. "Aaron's book is the gold standard for Mac OS X programming books-beautifully written, and thoughtfully sculpted. The best book on Leopard development."--Scott Stevenson, www.theocacao.com "This is the first book I'd recommend for anyone wanting to learn Cocoa from scratch. Aaron's one of the few (perhaps only) full-time professional Cocoa instructors, and his teaching experience shows in the book."--Tim Burks, software developer and creator of the Nu programming language, www.programming.nu "If you're a UNIX or Windows developer who picked up a Mac OS X machine recently in hopes of developing new apps or porting your apps to Mac users, this book should be strongly considered as one of your essential reference and training tomes." -Kevin H. Spencer, Apple Certified Technical Coordinator If you're developing applications for Mac OS X, Cocoa® Programming for Mac® OS X, Third Edition, is the book you've been waiting to get your hands on. If you're new to the Mac environment, it's probably the book you've been told to read first. Covering the bulk of what you need to know to develop full-featured applications for OS X, written in an engaging tutorial style, and thoroughly class-tested to assure clarity and accuracy, it is an invaluable resource for any Mac programmer. Specifically, Aaron Hillegass introduces the three most commonly used Mac developer tools: Xcode, Interface Builder, and Instruments. He also covers the Objective-C language and the major design patterns of Cocoa. Aaron illustrates his explanations with exemplary code, written in the idioms of the Cocoa community, to show you how Mac programs should be written. After reading this book, you will know enough to understand and utilize Apple's online documentation for your own unique needs. And you will know enough to write your own stylish code. Updated for Mac OS X 10.4 and 10.5, this revised edition includes coverage of Xcode 3, Objective-C 2, Core Data, the garbage collector, and CoreAnimation